Rhino Mano Ventures : Genius Purse Tracker / Muhamad Alif Hanifa Mohd Asri [et al.] - Mohd Asri, Muhamad Alif Hanifa; Shahrul, Mohd Aufa; Mohd Yussof, Muhamad Amer Ikhram; Zulkifli, Nur syahmina (2019)
The leather wallet industry is an expansive and resistant industry where the demands are increasing constantly due to the increase in population. This industry is one of the influential industries to the income of the nation. On top of that, with electronic industry, it can improve living standards foster the growth of the leather wallet and goods market. Global market players continuously launch latest and stylish leather goods according to the changing demand of consumers. The wallet is made from premium and high quality of leather which follow the changing of fashion trends. Apart from that, it also provides GPS tracker and Bluetooth buzzer to help the user that lost their wallet or purse. In Malaysia, this product is recent introduced to the people either children or teenagers nor adults and older .With the increase in population, the demand of this product will very much likely to be increased. The production of genius purse tracker has long shelf life and has the potential to be exported to other countries. This allows our company to sell the products overseas increasing the market size and sales of company